Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray terhadap Hasil Belajar Siswa pada Pembelajaran Tematik di Kelas V SDN Gugus XIX Kota Bengkulu - Tiya Anjani; Nani Yuliantini; Abdul Muktadir (JURIDIKDAS, 2021)
The study aimed to determine the effect of Two Stay Two Stray cooperative learning model on student learning outcomes in Thematic learning in V class SDN Gugus XIX of Bengkulu City. This research was quantitative research. The research method was quasi-experimental with the type of design matching onle pretest-posttest control group design. The population of this study were five grade in Gugus XIX of the city of Bengkulu City. The sample in this study were VC class SDN 71 Bengkulu City and V class SDN 103 Bengkulu City. The sampling technique used cluster random sampling. The research instruments was a knowledge learning result is multiple choice questions (pretest and posttest). For the attitude and skills aspects used is observation sheets. The data analysis by using descriptive statistics and inferential statistic. The results shows that the t-test score obtains in the Indonesian language is 4.012 and in the natural science is 2,941 with t-tables at the 5% significance level of, 1,669 where t-count is greater than t-table. It can be concluded, that there is a significant effect on student learning outcomes in Thematic learning using the type Two Stay Two Stray cooperative leaning model.Keywords: Cooperative Learning Model Type Two Stay Two Stray, Thematic, Learning Outcomes